Performance enhancement of 10 Gbps OCDMA Networks usingDPSK and DQPSKwith Unique code-sequence - Go, Yun Ii; Thio, Tzer Hwai Gilbert; Dimyati, K. (Trans Tech Publications Ltd, 2014)
This paper demonstrates the achievable performance enhancement in a multi-user network using optical unique code sequences. The study is conducted in a four-user Metropolitan Area Network (MAN) with a transmission rate of 10 Gbps. This paper investigates the feasibility of implementing Differential Phase Shift Keying (DPSK) and Differential Quadrature Phase Shift Keying (DQPSK) technique to replace conventional techniques such as On-Off Keying (OOK) and Amplitude Shift Keying (ASK). The performance of the integrated formulation of optical unique code sequenceswith DPSK and DQPSKtechnique is evaluated by determining the Bit Error Rate (BER) for various configurations and transmission distances up to 100 km.